ANALYSIS OF READING ABILITY FOR CLASS 1 STUDENTS AT BANYUAJUH 2 ELEMENTARY SCHOOL - Hellinia Yuyun; Rika Wulandari (Citra Dharma Cindekia, 2022)
Reading is a process carried out to practice communication skills. Reading skills are needed early on to get the message a writer wants to convey. The ability to read is very beneficial for everyone, especially children in elementary school education. Reading skills are needed to keep up with the times, because by reading someone will gain new knowledge and experience. This study aims to determine the level of reading ability of grade 1 students at Banyuajuh 2 Elementary School and what factors influence this reading ability. This type of research used descriptive qualitative research, with data collection using interviews and reading tests. This research involved seven grade 1 students at Banyajuh 2 Elementary School. Based on the results of the research, it can be concluded that the reading skills of grade 1 students at Banyuajuh 2 Elementary School still need to be improved because there are some students who are not fluent or even unable to read. The factors that cause students to experience reading delays are environmental factors outside of school and within school, for example inadequate school facilities, lack of support from parents, and lack of strategies and print and non-print media play an important role in improving children's reading skills.